Foreign capital penetration and financial market development in developing countries Case study of Turkey 1989-2010 - Bulut, Nihan (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
Gelişen ülkelerde yabancı sermaye girişini ve finansal piyasa gelişimini: Örnek çalışma Türkiye 1989-2010